2019
DOI: 10.1002/cre2.253
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of clinical symptoms of chemotherapy‐induced oral mucositis in adult patients with acute leukemia: A preliminary study

Abstract: Objective The objective of this study was to prospectively evaluate the clinical features of chemotherapy‐induced oral mucositis (CIOM) in adult patients with acute leukemia and the aggravating factors for such symptoms. Subjects Thirty‐seven prospective patients aged ≥19 years with acute leukemia undergoing chemotherapy were enrolled. Oral and clinical investigations were performed at baseline and on Day 14 after starting chemotherapy. The presence and severity of cancer‐induced oral mucositis were demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In our series, we found a correlation between mucositis and type of therapy [Intensive chemotherapy 20 (27%); non-intensive treatment 4 (14%); support care 2 (7%); p=0.04; in line with literature data, indicating a mucositis incidence of 20-40% in patients receiving standard chemotherapy and <5% receiving CPX-351 [23][24][25] ]. However, this is not reflected in the correlation between the type of therapy and MDRO colonization (p=0.2).…”
Section: Methodssupporting
confidence: 89%
“…In our series, we found a correlation between mucositis and type of therapy [Intensive chemotherapy 20 (27%); non-intensive treatment 4 (14%); support care 2 (7%); p=0.04; in line with literature data, indicating a mucositis incidence of 20-40% in patients receiving standard chemotherapy and <5% receiving CPX-351 [23][24][25] ]. However, this is not reflected in the correlation between the type of therapy and MDRO colonization (p=0.2).…”
Section: Methodssupporting
confidence: 89%
“…In this study, the WHO classification was used to select patients, which is a combination of objective criteria such as mucosal changes including redness and ulcers and functional criteria such as inability to eat. Studies have shown that this criterion is significantly correlated with the clinical signs and symptoms of mucositis ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Buccal mucosa, lips, soft palate, and the ventral side of the tongue as well as floor of the oral cavity are usually affected [31]. According to the World Health Organization (WHO) criteria for the assessment of toxic effects of cytostatics on oral tissues, mucositis is defined from individual painless ulceration to highly prominent erythema and edema of oral mucosa with multiple, extremely painful ulcerations that require the application of enteral or total parenteral nutrition [27,32,33]. Mucositis is more common in young people due to increased mitotic activity of oral epithelial cells in younger age.…”
Section: Oral Changes Before Transplantation Of Hematopoietic Stem Cellmentioning
confidence: 99%